David Shatz: Torah, philosophy, and culture - Tirosh-Samuelson, Hava; Hughes, Aaron W. (Library of contemporary Jewish philosophers 2213-6010, 2016)
"David Shatz is the Ronald P. Stanton University Professor of Philosophy, Ethics, and Religious Thought at Yeshiva University. With rabbinic ordination earned at Yeshiva University and a Ph. D. with distinction in philosophy from Columbia University, Shatz is committed to integrating Judaism and secular wisdom. An analytic philosopher as well as a Jewish philosopher, he has written extensively on free will, ethics, epistemology, medieval and modern Jewish philosophy, and philosophy of religion. His writings cover such topics as autonomy, altruism, philosophical skepticism, science and Judaism, peer review, theodicy, biblical interpretation, Maimonides, modern rabbinic figures, messianism, fanaticism, religious diversity, and theology. Shatz is also editor of the MeOtzar HoRav series, which publishes manuscripts of Rabbi Joseph B. Soloveitchik, and is editor of the Torah u-Madda Journal"--